Pengaruh Employee Engagement dan Dukungan Fasilitas terhadap Efektivitas Kinerja Pegawai Penyandang Disabilitas Pemerintahan Kota Surabaya - Artika, Tiara; Nadiya Hime, Zahra; Amaniah, Desy; Varah Nur A, Melissa; Amalia Jeany P, Jacinda (Jurnal Administrasi Publik dan Bisnis, 2025)
This study aims to analyze the influence of employee engagement and facility support on the effectiveness of the performance of employees with disabilities in the Surabaya City Government. The background of this study is based on the importance of realizing an inclusive and fair work environment, considering the low representation and effectiveness of the performance of employees with disabilities in the public bureaucracy. The method used is a quantitative approach with a survey technique using a questionnaire distributed to 103 respondents with disabilities. Data were analyzed through multiple linear regression using Jamovi software. The results of the study indicate that employee engagement and facility support have a significant effect both simultaneously and partially on performance effectiveness. The Adjusted R Square value of 0.991 indicates that 99.1% of the variation in performance effectiveness can be explained by the two independent variables. This finding strengthens the relevance of Herzberg's theory and the theory of service quality (Parasuraman et al.), which states that intrinsic factors and work environment conditions have an important role in improving employee performance. This study recommends the formulation of evidence-based policies that emphasize empowerment, active involvement, and the provision of adaptive work facilities for employees with disabilities, in order to encourage transformation towards an inclusive and productive bureaucracy.